STUDI KASUS DI SEKOLAH: PERAN PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM DALAM PROSES PEMBELAJARAN - Rosfiani, Okta; Iqbal, Ros Muhammad; Syahputra, Muhammad Faizal Ilham Ryannico; Pohan, Fela Dewita; Aminah, Nur (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
Teacher professionalism is part of increasing the standardization of knowledge that has a significant effect on the student learning process. This study aims to determine the influence of the role of professional Islamic Religious Education teachers who have followed the standardization in increasing knowledge as professional teachers at SMAN 1 Rumpin Bogor and its influence on the learning process. The research method used document analysis both from lesson plans, and relevant literature related to the research topic. Documents were collected from the main source, namely school institutions in the form of documents and analyzed to interpret the contents of the documents by triangulating other data sources. The results of this study indicate that the role of professional teachers and support from institutions in improving the professional standardization of Islamic Religious Education teachers is indispensable because it can affect and improve the effectiveness of the student learning process from student learning achievement. The findings emphasize the importance of teacher professional improvement and continuous training. Teachers can master the material, structure, concepts, and scientific mindset that support the subjects they teach in the learning process. This finding provides an understanding that there is a need to improve the professionalism of Islamic Religious Education teachers in schools.